African Enterprises: Receptacles of Conciliation Mechanisms - Jean Biwolé Fouda; Gabriel Etogo (M@n@gement)
The aim of this paper is to determine the common categories that pertain to the unique nature of enterprises in Africa. To do this, we carried out ethnographic studies in eight enterprises selected in different countries in order to identify the social systems and shared or mediating structures that constitute the embeddedness of business owners’ behaviors. The results of this investigation lead us to view enterprises in Africa as receptacles of conciliation mechanisms. Precisely, this involves their shared destiny, history, strong durability, trust in the given word, and attachment to tradition. The economic reality of entrepreneurship in Africa is thus different from the fragmented image traditionally put forward in economics.